Analisis Sistem Sertifikasi Halal Kategori Self Declare - Arifin, Hafiznur (CV. Lafadz Jaya, 2023)
With the increasing population of Muslims in the world, the need and demand for products that are guaranteed halal is very large. Every product that will be marketed to Muslims must have a halal certification issued by an institution that has the authority in halal certification. However, the offer of halal products is still very lacking. On the basis of these problems, the Provider Agency Halal Product Guarantee (BPJPH) makes a policy for a halal certification scheme with the